2018
DOI: 10.3389/fnins.2018.00525
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Prediction of Brain Disorders Using Functional Connectivity: Promising but Challenging

Abstract: Brain functional imaging data, especially functional magnetic resonance imaging (fMRI) data, have been employed to reflect functional integration of the brain. Alteration in brain functional connectivity (FC) is expected to provide potential biomarkers for classifying or predicting brain disorders. In this paper, we present a comprehensive review in order to provide guidance about the available brain FC measures and typical classification strategies. We survey the state-of-the-art FC analysis methods including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
232
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(234 citation statements)
references
References 295 publications
(349 reference statements)
2
232
0
Order By: Relevance
“…However, a growing body of evidence suggests that rsfMRI is dynamic in nature [Allen et al, ; Hutchison et al, ; Wee, Yap, & Shen, ]. Recently, researchers have shown more interest in dynamic functional connectivity (DFC) studies and found profound indicators associated with DFC [Du, Fu, & Calhoun, ; Preti, Bolton, & Van De Ville, ]. Meanwhile, DFC was superior to SFC at predicting behavior in a typically developing (TD) population [Chen, Nomi, Uddin, Duan, & Chen, ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing body of evidence suggests that rsfMRI is dynamic in nature [Allen et al, ; Hutchison et al, ; Wee, Yap, & Shen, ]. Recently, researchers have shown more interest in dynamic functional connectivity (DFC) studies and found profound indicators associated with DFC [Du, Fu, & Calhoun, ; Preti, Bolton, & Van De Ville, ]. Meanwhile, DFC was superior to SFC at predicting behavior in a typically developing (TD) population [Chen, Nomi, Uddin, Duan, & Chen, ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have extended towards using restFC to quantitatively predict or classify age-related conditions (Dosenbach et al, 2010;Woo et al, 2017;Du et al, 2018). However, failures of predictive models generalizing out-of-sample (Onoda et al, 2017;Teipel et al, 2017;Fountain-Zaragoza et al, 2019) highlight limitations of entirely data-driven approaches to predicting Alzheimer's-related pathologies, especially as artifactual contaminants of restFC can drive clinical group differences (Siegel et al, 2016;Hodgson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on functional connectivity have reported accuracies in the range of 60-95% in classifying schizophrenia versus healthy subjects(Du, Zening, & Calhoun, 2018;Woo, Chang, Lindquist, & Wager, 2017); however, most of them employ ICA to define networks from the whole data, which leads to a bias in the cross validation. Previous studies on functional connectivity have reported accuracies in the range of 60-95% in classifying schizophrenia versus healthy subjects(Du, Zening, & Calhoun, 2018;Woo, Chang, Lindquist, & Wager, 2017); however, most of them employ ICA to define networks from the whole data, which leads to a bias in the cross validation.…”
mentioning
confidence: 99%